Pattern, Distribution, and MRI Characteristics of Modic Changes in Patients with Low Back Pain: A Prospective 3 Tesla MRI Study - K.C., Rajendra; Yadav, Subhash Chandra; Rawal, Sanju; Oli, Bardan; Thapa, Krishna; Jha, Ranjit Kumar; KC, Geson Dhoj; Mukhi, Sadhan (Journal of National Heart and Lung Society Nepal, 2026)
INTRODUCTION Low back pain is one of the most prevalent musculoskeletal conditions. Modic changes are vertebral endplate and marrow signal alterations on MRI and reflect intervertebral disc degeneration and potential pain generators. Type 1 Modic changes represent inflammatory marrow edema and are particularly associated with active low back pain and inflammatory processes. Modic changes are classified based on combined T1- and T2-weighted MRI signal characteristics. Although conventional T1- and T2-weighted sequences remain essential for classification, subtle inflammatory changes may not always be clearly visualized. STIR imaging, with fat suppression and high sensitivity to edema, may improve lesion conspicuity. This study evaluated the pattern, distribution, and MRI characteristics of Modic changes on T1-, T2-, and STIR sequences using 3 Tesla MRI. MATERIAL AND METHODS A prospective study was conducted among 101 consecutive low back pain patients demonstrating Modic changes on lumbar MRI using 3 Tesla MRI at the Department of Radiodiagnosis and Medical Imaging, UCMS-TH, Nepal. Patients aged 34-81 years referred for MRI evaluation of low back pain were enrolled. Modic changes were evaluated according to type, vertebral level, and imaging characteristics on T1-weighted, T2-weighted, and STIR sequences. Descriptive statistics and chi-square tests were used for data analysis. RESULTS Modic Type 2 changes were the most common, observed in 60 patients (59.4%), followed by Type 1 in 31 patients (30.7%) and Type 3 in 10 patients (9.9%). The L4-L5 and L5-S1 vertebral levels were most frequently involved. The observed MRI signal characteristics were consistent with the established Modic classification. STIR hyperintensity was observed exclusively in Type 1 changes, improving visualization of inflammatory marrow edema. A significant association was observed between age group and Modic change type (p < 0.001), with Type 1 changes more common in younger patients and Type 2 and Type 3 changes increasing with age. CONCLUSION In this 3Tesla MRI study of patients with low back pain, Type 2 Modic changes were most frequent (59.4%), followed by Type 1 (30.7%) and Type 3 (9.9%). The L4–L5 level was the most commonly involved site (57.4%). STIR hyperintensity was observed only in Type 1 changes, aiding identification of inflammatory marrow edema. A significant association was found between age group and Modic change type (p < 0.001). STIR imaging may be a useful complementary sequence in routine lumbar spine MRI protocols, particularly when inflammatory Modic Type 1 changes are suspected.